N, N‐Diphospholylamines—A New Family of Ligands for Highly Active, Chromium‐Based, Selective Ethene Oligomerisation Catalysts. Issue 10 (21st June 2013) - Stennett, Tom E.; Hey, Thomas W.; Ball, Liam T.; Flynn, Stephanie R.; Radcliffe, James E.; McMullin, Claire L.; Wingad, Richard L.; Wass, Duncan F.
Abstract A series of new diphosphazane (PNP) ligands that contain 2, 3, 4, 5‐tetraethylphosphole or dibenzophosphole moieties has been synthesised. The new compounds have been screened for chromium‐catalysed, selective ethene oligomerisation by in situ combination with CrCl3(thf)3 and methylaluminoxane (MAO). The ligands derived from 2, 3, 4, 5‐tetraethylphosphole produce highly active catalysts for ethene oligomerisation, which show excellent selectivity to C6 and C8 linear α‐olefins. Complexes of the form [Cr(CO)4L] were synthesised and studied by IR spectroscopy and single‐crystal XRD. Variable‐temperature NMR spectroscopy was used to investigate restricted PN rotation in compounds with bulky nitrogen substituents.